Thermal alteration of water extractable organic matter in climosequence soils from the Sierra Nevada, California. Issue 11 (22nd November 2016) - Santos, Fernanda; Russell, David; Berhe, Asmeret Asefaw
Abstract: In the next decades, the influence of wildfires in controlling the cycling and composition of soil organic matter (SOM) globally and in the western U.S. is expected to grow. While the impact of fires on bulk SOM has been extensively studied, the extent at which heating of soil affects the soluble component of SOM remains unclear. Here we investigated the thermal transformations of water‐extractable organic matter (WEOM) by examining the changes in the distribution of carbon (C) functional groups in WEOM from soils heated at low and intermediate temperatures. WEOM (<0.7 µm particle size) was extracted from topsoils (0–5 cm depth) of five soil series formed from a nonglaciated granitic bedrock and sampled along a Sierra Nevada climosequence. Soils were heated in a muffle furnace at 150°C, 250°C, and 350°C for 1 h. The extracted solution was analyzed for WEOM aromaticity, mean molecular weight, organic C (OC) concentration, and major structural components by employing optical spectrophotometry and liquid‐state 1 H‐NMR spectroscopy. At 150°C and 250°C, OC concentrations increased relative to the thermally unaltered samples, with losses of oxygenated functional C groups and enrichment of aliphatic C structures observed at 250°C. Conversely, OC concentration and mean molecular weight decreased as heating increased from 250°C to 350°C, whereas WEOC became more enriched in aromatic C structures. Our results suggest that low and intermediate fire intensities significantly alter the nature of dissolved organic matter exported from soils to rivers in the Sierra Nevada and beyond. Key Points: Oxygenated and aliphatic structures dominated water extractable organic matter at 150°C Water extractable organic matter became more enriched in aromatic structures at 350°C Low and intermediate fire intensities change the amount and nature of soluble carbon transported from soils to rivers